Actitud natural y actitud fenomenológica - Rabanaque, Luis Román (Sapientia, 2011)
Husserl’s phenomenology takes as its point of departure the issue of knowledge in order to reformulate the idea of philosophy as a rigorous science which ultimately aims to establish an ethically good life founded on rational grounds. To that end it must face both the questions of the beginning and the method of philosophy, which in turn leads to take the difference between natural and philosophical attitude into account insofar as the phenomenological epokhè that makes reduction possible requires noting, thematizing and suspending the validity of the natural attitude. In the first section of this paper the essential features of attitudes are disclosed and different kinds of attitudes are distinguished. In the second section the natural attitude is shown to be the back- and underground for all special attitudes and its most remarkable features are outlined. Finally, the third section contrasts this basic natural attitude with the phenomenological attitude in connection with the way Descartes understands the questions of beginning and method. This allows to turn back to the problem of philosophy as knowledge oriented towards an ethical renewal of spiritual life, in order to show why the transit from natural to phenomenological attitude is the necessary condition for leaving behind the naïve standpoint on the unquestioned world-ground.